In situ and operando characterization techniques for nanocatalyst-based electrochemical hydrogen evolution reactions - Anaclet Nsabimana; Yiran Guan; Guobao Xu (Journal of Electrochemical Science and Engineering)
The hydrogen evolution reaction is important in energy conversion and storage. This has led to the design of different types of catalysts and production setups. Understanding the status of the catalysts and reaction mechanisms motivated researchers to adopt the operando/in situ techniques. Herein, we present a brief overview of the recent (from 2020) advances in the use of in situ and operando characterization techniques, such as in situ X-ray absorption spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction analysis, IR spectroscopy, electrochemical Raman spectroscopy, online inductively coupled plasma - mass spectroscopy, differential electrochemical mass spectroscopy, optical microscopy, electron microscopy, electrochemical atomic microscopy, electrochemical scanning tunneling microscopy, and scanning electrochemical microscopy, in the electrochemical hydrogen evolution reaction. Representative examples of the applications of these techniques are also provided. Challenges in this field and future perspectives are discussed.